Differential diagnosis of erythema migrans - Weber, K... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
The diagnosis of erythema migrans (EM) has to be made clinically as immunological tests are usually negative. It is possible to cultivate Borrelia burgdorferi from EM lesions, however this test is being done only in certain laboratories, it is time-consuming and expensive. A certain number of skin conditions may mimic EM, therefore a sufficient experience in dermatology is necessary.
Keywords: Diagnosis; Diagnosis, differential; Erythema chronicum migrans